Role of oxidative stress in pathophysiology of rheumatoid arthritis: insights into NRF2-KEAP1 signalling - Gurjasmine Kaur; Aman Sharma; Archana Bhatnagar (Taylor & Francis Group, 2021)
Rheumatoid arthritis is one of the most prevalent, chronic, inflammatory disorders involving multiple articular and extra-articular complications. Immune deregulation owing to a combinatorial network of cells, inflammatory components, degrading enzymes, angiogenetic factors, exhibiting pleiotropy, synergy, or redundancy, is a critical hallmark for synovial inflammatory milieu reasoning clinical heterogeneity and variability of the disease. As a prototype of autoimmune disease, the pathophysiology of rheumatoid arthritis has been linked to oxidative stress. However, the exact mechanism for these potential driving factors contributing to disease inception and perpetuation is yet elusive. Nuclear factor erythroid 2-related factor 2 - Kelch ECH associating protein 1 (Nrf2-Keap1) pathway, controlled via multifactorial regulation, functions as a ubiquitous, evolutionarily conserved intracellular defense mechanism. Nrf2-Keap1 signalling maintains homeostatic responses against a plethora of environmental or endogenous deviations in cellular growth, death, redox metabolism, inflammation, bone remodelling, detoxification, etc. Administration of antioxidants as an add-on pharmacotherapy along with conventional drugs has been elucidated as a better measure for disease management. Some of the most promising natural and synthetic redox-based therapeutic compounds function as either scavengers of reactive species, or inhibitors of their sources, or activators of an endogenous antioxidant system (Nrf2-Keap1). The present review focuses on the binomial "rheumatoid arthritis-oxidative stress", bringing insights into their pathophysiological interrelationships and Nrf2 signalling, as well as the implications of potential diagnostic oxidative stress biomarkers and therapeutic interventions directed for disease management in patients with rheumatoid arthritis.Highlights: RA has complex etiopathogenesis, evolving from multiple endogenous and exogenous factors with oxidative stress as a critical pathogenic signature. Oxidative damage and damaged compounds could serve as potent biomarkers for disease diagnosis, therapeutic response, and prognosis. One of the supreme cytoprotective signalling cascades, the Nrf2-Keap1 pathway has been known to elicit a protective effect against RA and various other autoimmune, inflammatory, degenerative disorders. Inclusion of natural and synthetic antioxidants has been encouraged by various studies for additional therapy to conventional drugs for better management of the disease.